2016
DOI: 10.1186/s12866-016-0623-9
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of in vitro agar based screens to characterize the anti-fungal activities of bacterial endophyte communities

Abstract: BackgroundEndophytes are microbes that inhabit internal plant tissues without causing disease. Plant microbial communities consist of large numbers of endophyte species. Understanding the functions of these endophytes is a major challenge. An important function of some endophytes is to suppress fungal pathogens. Typically, plant associated microbes are screened for anti-fungal activities in vitro using the high-throughput dual culture screen, but it is not clear whether this method correlates with the activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Using the agar disk diffusion technique ( Shehata et al, 2016 ), the tested soil-borne fungal plant pathogens and oomycetes were grown in YPD broth (#Y1375, Sigma–Aldrich) for 3–5 days (based on the fungus growth rate) at 25°C with gentle shaking. Pre-melted cooled PDA media was inoculated with the mycelia (25 ml/150 ml PDA for R. solani , 1 ml/50 ml PDA for P. capsici and F. graminearum , and 1 ml/100ml PDA for P. aphanidermatum ) and 50 ml were poured into each sterile Petri dish (150 mm × 15 mm), then left to solidify.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the agar disk diffusion technique ( Shehata et al, 2016 ), the tested soil-borne fungal plant pathogens and oomycetes were grown in YPD broth (#Y1375, Sigma–Aldrich) for 3–5 days (based on the fungus growth rate) at 25°C with gentle shaking. Pre-melted cooled PDA media was inoculated with the mycelia (25 ml/150 ml PDA for R. solani , 1 ml/50 ml PDA for P. capsici and F. graminearum , and 1 ml/100ml PDA for P. aphanidermatum ) and 50 ml were poured into each sterile Petri dish (150 mm × 15 mm), then left to solidify.…”
Section: Methodsmentioning
confidence: 99%
“…Primary screening of potentially beneficial microbes for antagonism of culturable phytopathogens is typically performed using the in vitro dual culture assay where the pathogen target and the candidate biocontrol agents are cultured together to assay for direct pathogen growth suppression ( Pliego et al, 2011 ; Bosmans et al, 2016 ). This method has been shown to predict their interactions in planta ( Shehata et al, 2016 ). As this option is not available for obligate pathogens such as P. xanthii , leaf disk and detached plant organ assays are used where the pathogen is maintained on plant tissues in Petri dishes supplemented with water and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic Bacillus altitudinis served as elicitors of biomass and ginsenoside production [ 13 ]. Bacterial endophytes from Zea displayed anti-fungal activity against two fungal pathogens [ 40 ]. Li et al have reported that the domain genera included Rhizobium , Sulfurospirillum , Uliginosibacterium , Pseudomonas , Aeromonas and Bacteroides , all of which could fix nitrogen and improve plant growth [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that M. incognita pioneer genes encoding effectors act as potential host specificity determinants (Jaouannet et al, 2012 ; Rutter et al, 2014 ; Xie et al, 2016 ; Nguyen et al, 2017 ). Herein, transcriptional expression analysis reveals that MiPM is highly expressed at the parasitic J2 stage, when the nematode secretes massive amounts of effectors and promotes the formation of the giant cells (Sijmons et al, 1994 ; Hewezi, 2015 ; Rehman et al, 2016 ). Our data indicates that the putative secreted MiPM protein acts during nematode infection but without triggering HR.…”
Section: Discussionmentioning
confidence: 99%
“…Many nematode effectors manipulate different cellular pathways such as hormone signaling, protein post-translational modifications, redox signaling, cell wall modifications, or metabolism (Goverse and Smant, 2014 ; Hewezi, 2015 ; Holbein et al, 2016 ; Ali et al, 2017 ). While some of nematode effectors share similarities with known proteins, most of them are pioneer proteins making their characterization more challenging (Danchin et al, 2013 ; Rehman et al, 2016 ; Kikuchi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%